Views sought on equine trading scheme (Veterinary record, 2011)
Under its proposals, members registering for the scheme would have to adhere to a number of conditions: * Horses on the registered premises would have to meet scheme standards at all times and be subject to independent audit; Each member would have to nominate a veterinary practice that would be involved in the care of the horses on the registered premises; All horses on the registered premises would have to be identified by a passport and microchip; Members would either have to have their own microchip reader or have access to a reader; Members could only sell animals in the scheme that were in good health and showed no signs of illness.